Analisa Perbandingan Kuat Sinyal Antara Operator Hutchison, Indosat, Telkomsel, Dan Xl Axiata Dengan Menggunakan Software RF Signal Tracker Di Area Jalan Protokol Pekanbaru - Chandra, Chandra; Rahayu, Yusnita; Anhar, Anhar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Cell phones have become a major part of the society in daily life - today. The use of mobile phones has spread in every community, rural and urban. SingTel, Hutchison, Comindo Axiataand Indosat are some operators cellular telecommunications network that use UMTS and HSDPA technology. The parameters that determine the power level and the quality of the signal strenght of each operator is known as RxLevel (the Receptiom Level) for GSM and the RSCP (Received Signal Code Power) in order to WCDMA. One of methods for analyzing to measure that parameters is a drive test which use rf signal tracker software. This research will compare a drive test method with simulation method, where the simulation using radio mobile software. The location of this research is in some protocol streets on Pekanbaru, such as Cut Nyak Dien Street, Jend. Ahmad Yani Street, Ir. H. Juanda Street, Gajah Mada Street, Diponegoro Street and Jend. Sudirman Street. The result shows that Telkomsel has the best signal strength in protocol streets on Pekanbaru with -63.082 dBm, followed by XL Axiata with -68.187 dBm, then Hutchison with -75.082 dBm. The lowest signal strenght is operator Indosat with the value -86.411 dBm.Keywords: WCDMA, UMTS, HSDPA, Drive Test, RF Signal Tracker, Radio Mobile.